How Artificial Intelligence Can Empower the Robotic Recycling Industry: Toward an Adaptive, Data-Driven, and Circular Material Recovery System - Cai, Chengyao (Computers and Artificial Intelligence, 2026)
This paper examines how artificial intelligence (AI) can strengthen the robotic recycling industry by improving material identification, adaptive sorting, process optimization, and data-driven decision-making across recycling systems. As waste streams become more heterogeneous and contaminated, conventional recycling methods—particularly manual sorting and rigid automation—face growing limitations in throughput, consistency, and economic viability. Drawing on recent institutional reports and academic research, this paper argues that AI-enabled robotics offers a socio-technical pathway for transforming recycling into a more adaptive and resilient material recovery system. Specifically, AI improves robotic recycling through enhanced perception and classification, real-time response to variable feedstocks, higher-speed sorting with quality control, and cumulative operational learning. The paper also analyzes barriers to large-scale adoption, including capital intensity, infrastructure readiness, model reliability under domain shift, workforce transition challenges, and governance requirements. It further argues that the long-term effectiveness of AI-powered robotic recycling depends on integration with policy incentives, standards, and circular economy objectives rather than technology deployment alone. Overall, the study concludes that AI can serve as a powerful enabler of robotic recycling when implemented as part of a broader socio-technical system that combines technical innovation, institutional support, and responsible governance.